PENDIDIKAN KARAKTER DAN ETIKA DALAM PENDIDIKAN - Yusri Fajri Annur; Ririn Yuriska; Shofia Tamara Arditasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2021)
The problem regarding the challenges of education in the future lies in the effort to prepare a nation that has character so that it can answer the various problems of the times. The education that is given should not only emphasize knowledge and memorization of students, but rather on values and ways of thinking in order to become a superior human with character. Ethics and values can be provided effectively by integrating character education. Pancasila moral education, and religious education. Relevant to the character education process as an effort to implement character values for future candidates for the nation. Educational ethics is based on a real study that humans must take action based on ethics, including the teaching and learning process in education. There is a common mistake in society as an educational field where practicing education does not provide correct ethical values as an educational basis. This condition will continue from generation to generation and its influence will continue and produce moral damage for the next generation, including educators. Therefore, in an effort to overcome the moral crisis in the world of education, a character education model that is based on the word of God, Pancasila and the noble values of national culture (adat) must be applied.